Macro-anatomical investigations on the hind limb skeleton of mole-rat (Spalax leucodon Nordmann) - Özkan, Zait Ender (My University, 2002)
In this study, five mole-rats (Spalax leucodon Nordmann) were used to investigate the bones of hind limb. Almost the whole area of the sacropelvic surface (facies sacropelvina) was formed by the iliac tuberosity (tuberositas iliaca). Average distance between the midacetabulum and tuber coxae was 16.7 mm, and average distance between the midacetabulum and tuber ischiadicum was 7.9 mm. There were three prominent trochanters on the femur. Eight distinct tarsal bones and five distinct metatarsal bones were present. The shortest metatarsal bone was os metatarsale I and the longest was os metatarsale III. The pedis was complete with five digits. There were two phalanges in the first digit and the other four digits were composed of three phalanges.
Keywords: Anatomy; Mole-rat; Ossa membri pelvini; Spalax leucodon Nordmann